Development of reduced and optimized reaction mechanism for potassium emissions during biomass combustion based on genetic algorithms. (15th November 2020) - Wan, Kaidi; Vervisch, Luc; Gao, Zhenxun; Domingo, Pascale; Jiang, Chongwen; Xia, Jun; Wang, Zhihua
Abstract: A reduced mechanism for potassium chemistry under combustion conditions is derived from a detailed chemical mechanism for alkali metal emissions (Glarborg and Marshall, 2005), which could be useful for three-dimensional (3D) numerical simulations of potassium emissions by biomass combustion furnaces. An automated chemistry reduction and optimization approach relying on canonical micro-mixing problem is applied to develop the reduced mechanism, whose performance is then evaluated in two-dimensional (2D) carrier-phase direct numerical simulation (DNS) of pulverized-biomass combustion. Good agreement is achieved between predictions of the reduced and the detailed mechanisms on the four major potassium species, i.e., K, KOH, KCl and K2 SO4 . The prediction capabilities of the reduced mechanism for various K/Cl/S ratios in the volatiles are further investigated by a parametric study with 14 two-dimensional DNS cases. The potassium chemistry under those various conditions are well predicted by the reduced potassium mechanism with a CPU cost reduction reaching up to 71.3% compared to the detailed reference mechanism. Highlights: Systematic reduction study of detailed potassium mechanism is performed. Reduced mechanism is derived relying on canonical micro-mixing problem. Reduced mechanism is validated with DNS of biomass flames under various K/Cl/S ratios. A reduction of up to 71.3% in CPU cost is achieved with the reduced mechanism.